The In & Between: Weaving social interaction through mixed-use development in Robertsha - Ashton, James (University of the Witwatersrand, Johannesburg, 2024)
Critically analysing the need for social interaction through communities. Robertsham is a location that contains a rich history dating back to 1948 when it was first established. The study focuses on the public park that splits the residential and industrial areas of Robertsham. The park was once a social interactive space for families within Robertsham and has now become a barren underutilised space. The design aims to include spaces that address an issue within each sector of Robertsham. A mixed-use development aided to serve the community as well as bring back the nature of the park with the main routes being social interaction, safety, and connection.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Architecture (Professional). School of Architecture and Planning. University of the Witwatersrand, Johannesburg, South Africa.
Keywords: Social Interaction; Socio-economic Theory; Recycling; Urban Farm; Safety; Community; Gathering; Weaving; Sustainability; Live; Work; Play; Robertsham; SDG-7: Affordable and clean energy